Genetic Transformation of the Filamentous Fungus Pseudogymnoascus verrucosus of Antarctic Origin - Díaz, Anaí; Villanueva, Pablo; Oliva, Vicente; Gil-Durán, Carlos; Fierro, Francisco; Chávez, Renato; Vaca, Inmaculada (Frontiers in microbiology, 2019)
Cold-adapted fungi isolated from Antarctica, in particular those belonging to the genus , are producers of secondary metabolites with interesting bioactive properties as well as enzymes with potential biotechnological applications. However, at genetic level, the study of these fungi has been hindered by the lack of suitable genetic tools such as transformation systems. In fungi, the availability of transformation systems is a key to address the functional analysis of genes related with the production of a particular metabolite or enzyme. To the best of our knowledge, the transformation of strains of Antarctic origin has not been achieved yet. In this work, we describe for the first time the successful transformation of a strain of Antarctic origin, using two methodologies: the polyethylene glycol (PEG)-mediated transformation, and the electroporation of germinated conidia. We achieved transformation efficiencies of 15.87 ± 5.16 transformants per μg of DNA and 2.67 ± 1.15 transformants per μg of DNA for PEG-mediated transformation and electroporation of germinated conidia, respectively. These results indicate that PEG-mediated transformation is a very efficient method for the transformation of this Antarctic fungus. The genetic transformation of described in this work represents the first example of transformation of a filamentous fungus of Antarctic origin.